Reducing the punch force in the circular punching process by preheating under the recrystallization temperature - Kurniawan, Yani; Mahardika, Muslim; Amrullah, Muhammad Haritsah; Cahyadi, Bambang (SINERGI, 2022)
Punch force is the main factor in the success of making holes using the punching process. However, the punching process cannot make a hole when the punch force in the machine is smaller than the punch force in the material. Preheating can be used to reduce the punch force in the material. This research aims to develop the preheating method with low current electricity for reducing the punch force in the material. The preheating method is used two tubular type heating elements with an electric current of about 0.9 A. This method can be heating the material below recrystallization temperature (100 and 150 °C). Preheating at 100 and 150 °C can reduce the punch force by 4 and 11% compared to without preheating. These results can be concluded the material heating below recrystallization temperature is effectively enough to reduce the punch force. Thus, the punching process is able to make a hole even though the punch force in the machine is smaller than the punch force in the material.